Karakteristik Hidrologi Tanah di Bawah Tegakan Pinus (Pinus merkusii), Merawan (Hopea odorata Roxb) dan Mahoni Uganda (Khaya anthoteca): Soil Hydrological Characteristics Under Pine (Pinus merkusii), Merawan (Hopea odorata Roxb), and African Mahogany (Khaya anthoteca) Stands - Andria Harfani Qalbi; Suria Darma Tarigan; Enni Dwi Wahjunie; Dwi Putro Tejo Baskoro (Jurnal Ilmu Tanah dan Lingkungan, 2018)
Forest destruction may affect forest hydrological functions either as a water regulator, maintaining the timing and distribution of river water flows, maintaining microclimate, or being able to protect the underlying areas from disasters such as floods. Revegetation is considered as an effort to improve the condition of forest and environment. The objective of this study was to examine the hydrological characteristics of soil under stands of Pinus (Pinus merkusii), Ugandan Mahogany (Khaya anthoteca), and Merawan (Hopea odorata Roxb). The method used is periodic measurement of soil physical variables. Our investigation reveals that hydrological and physical properties of soil under the stands were different. Within the same depth of soil, water content changed from the highest to the lowest in Pine (3.05%), Merawan Siput Jantan (2.40%), and African Mahogany (1.89%), respectively. The highest infiltration was 116.25 cm hour-1 under Pine stand, while the lowest was 24 cm hour-1 under Merawan Siput Jantan stand. The highest permeability was 13.27 cm hour-1 under Pine stand, while the lowest was 2.72 cm hour-1 under Merawan Siput Jantan stand. Dominated by clay, the soil texture was relatively similar in each stand. Further, the soil under the three stands were categorized as the soil hydrological group B.